Population Dose Distribution due to Soil Radioactivity in Designated and Undesignated Waste Dumpsites in the City of Lagos Nigeria: Radiation Absorbed Dose in Soil - Fawey, Ebenezer Babatope; Babalola, Ayo (Biological Sciences - PJSIR, 2010)
The radionuclide contents in soil from waste dumpsites in the city of Lagos were determined. The radioactivity concentration level due to 40K, 226Ra and 228Th in the soil were determined using gamma-ray spectrometry system. The average radioactivity level obtained was 1134 Bq/kg (designated dumpsite) and 1045Bq/kg (undesignated) for 40K, 43 Bq/kg (designated) and 85 Bq/kg (undesignated dumpsite) for 226Ra, 34 Bq/kg (designated) and 38 Bq/kg (undesignated dumpsite) for 228Th. No artificial radionuclide was detected in any of the samples. The average outdoor effective dose rate due to gamma exposure was calculated as 0.11 mSv/y at designated and 0.13 mSv/y at undesignated dumpsites. These values are much smaller than 1 mSv/y, the limit recommended for the member of the public by United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR).